Impact of Corporate Social Responsibility on the Profitability of Multinational Companies in Nigeria (Global Journal of Management and Business Research, 2017)
This study investigated the impact of corporate social responsibility (CSR) on profitability of multinational companies in Nigeria. Specifically the study analyzed the relationship and impact of corporate social responsibility spending on profit after tax, as well as the causal relationship between corporate social spending and profit after tax. Five multinational companies were randomly selected in the study and data were collated from their respective financial reports for a period of five years covering 2010 to 2014. The study employed techniques including correlation analysis, pooled ols estimation, fixed effect and random effect estimations, granger causality estimation and post estimation test such as restricted f-test and Hausman test. Result revealed that there is weak negative correlation between corporate social spending and profit after tax (-0.0648). Corporate social spending exerts negative insignificant impact on profit after tax (β=-27.0860, P=0.704), while there is only evidence for unidirectional causal relationship running from corporate social spending to profit after tax for Oando plc, among all the selected multinational companies (f-stat=208.868, P=0.0440).
Keywords: corporate social responsibility; profitability; multinational companies; csr spending